2006
DOI: 10.1007/s10388-006-0095-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Barrett's esophagus in Japan

Abstract: Norman Barrett originally described two special conditions, namely, a congenital short esophagus with an intrathoracic gastric columnar lining and congenital gastric heterotropia in the esophagus with ulceration. Thereafter, these conditions began to be known as "Barrett's esophagus." It is an acquired condition of esophageal columnar metaplasia following chronic gastroesophageal refl ux, and the classical Barrett's esophagus has been defi ned as having a circumferential columnar metaplasia spreading minimally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Sharma et al reported that endoscopists were not able to reliably measure short segments of BE (<1 cm) using the P-criteria (the kappa value was 0.21) [11]. In contrast, the J-criteria can more readily identify endoscopic BE segments of less than 10 mm, and it may also be able to identify ultra-short segments of BE more consistently [7]. Although the difference in the detection rate of BE of less than 10 mm between the J-criteria and the P-criteria was not significant, it tended to be higher using the J-criteria.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Sharma et al reported that endoscopists were not able to reliably measure short segments of BE (<1 cm) using the P-criteria (the kappa value was 0.21) [11]. In contrast, the J-criteria can more readily identify endoscopic BE segments of less than 10 mm, and it may also be able to identify ultra-short segments of BE more consistently [7]. Although the difference in the detection rate of BE of less than 10 mm between the J-criteria and the P-criteria was not significant, it tended to be higher using the J-criteria.…”
Section: Discussionmentioning
confidence: 94%
“…In Western countries, the prevalence of endoscopically suspected BE was reported to be approximately 10 % [6]. In a recent multicenter prospective Japanese study, the prevalence of endoscopically suspected BE was reported to be 24.1 %, of which 99.2 % were SSBE [7]. That was considerably higher than in Western countries.…”
Section: Introductionmentioning
confidence: 89%
“…The difference in the prevalence of SSBE seems to be caused by the difference in the defi nition of the esophagogastric junction (EGJ) and whether intestinal metaplasia is included. Kawano reviewed the prevalence of BE worldwide in detail and emphasized that the actual prevalence should be determined by a universally acceptable defi nition of BE because different defi nitions of BE have resulted in varying prevalence rates [2]. According to the American College of Gastroenterology guidelines [3], the variation of BE prevalence in Japan may be underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…According to the American College of Gastroenterology guidelines [3], the variation of BE prevalence in Japan may be underrepresented. On the other hand, the prevalence of classical BEs (long-segment Barrett's esophagus, LSBE) is relatively constant, with a range of 0.3%-0.6% in adults undergoing EGD in Japan [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation